Determination of vitamin D3 encapsulated in liprotide β-lactoglobulin crosslink oleic acid by HPLC and SEM - Sylvia Rahmi Putri; Gemala Anjani; Faizah Fulyani; Diana Nur Afifah; Ahmad Syauqy; Fitriyono Ayustaningwarno (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Vitamin D is an unstable compound to light, heat, and certain chemicals, so it is easily degraded under various conditions. Therefore, instability is achieved through the encapsulation method using complex protein carrier compounds with fatty acids known as liprotide. This study aims to determine vitamin D3. Method, the determination of vitamin D3 was analyzed, including the determination of vitamin D3 standard eluents, calibration curve, and determining the retention time of vitamin D3 encapsulated in liprotide using HPLC (High-Performance Liquid Chromatography). Morphology of vitamin D3 encapsulated in liprotide using SEM (Scanning Electron Microscopy). The results showed that the standard vitamin D3 HPLC analysis using acetonitrile: methanol and acetonitrile: aquabidest obtained two peaks. Butanol: n-hexane eluent obtained one peak with a retention time of 2,170 minutes. The results of the standard calibration curve for vitamin D3 at a linearity value of R2 = 0,9997 and f(x) = 14,928x-117,930. The same retention time was obtained for vitamin D3 encapsulated in liprotide. Conclusion, an enlargement of the cubic structure, which occurred due to the encapsulation of vitamin D3 by the liprotide-forming micelles.